The temptress in tweeds - Graiz, Zoey (Central Book Supply, Incorporated, 2015)
Appetizing...amusing...riveting...The Temptress in Tweeds is a compelling story anchoring in love. Effie is a head turner, in her own way. Although already in her mid-30's, she never had the official girlfriend title, even with her PhD. in Phallic Studies. She tried, in many ways but failed. Two of them even made a "Break Effie's Heart Day," a year apart. Her loneliness makes her think...should she just concede on being a girlfriend in bed? Or be persistent in unravelling the knots of her faith in love?